WAYS TO ENSURE SUSTAINABLE GROWTH OF COMMERCIAL BANKS' LOANS (American Journal of Business Management, Economics and Banking, 2023)
Ensuring the stable growth of commercial bank loans is one of the necessary conditions for improving the practice of financing investment costs of enterprises of the real sector of the national economy. Therefore, in the 2020-2025 strategy for reforming the country's banking system, ensuring stable and moderate growth of bank loans is recognized as one of the priority areas of banking system reform. In the article, the problems related to ensuring the stable growth of loans of the country's banks are identified and scientific proposals aimed at solving them are developed.